Performing economy differently: Exploring economic personhood and local economic diversity - McKay, Deirdre (The Australian Journal of Anthropology, 2009)
Many popular conceptions of economy now delimit what counts as the ‘real’ economy by capitalist enterprises, market transactions and wage labour. Anthropologists describe such ideas of economy as abstract, dis-embedded (Polanyi 1957a, b) or virtual (Carrier and Miller 1998), arguing that these conceptions are not adequate to the empirical realities of lived experience. Beyond anthropology, there is a growing literature that theorises the ways academic accounts have themselves brought a dis-embedded or virtual version of economy into being (Mitchell 2002, 2008; Callon 2005; Callon and Caliskan 2005; Latour 2005; Gibson-Graham 2006). Scholars advocating a performative approach argue that academic notions of economy are not simply descriptive of empirical realities, but actively shape those realities, giving form to the ways that a ‘real’ economy emerges from particular socio-cultural fields. In the context of applied development anthropology, a performative reading of economy offers a helpful platform for applied research directed towards diversifying local economic understandings and practices. This paper explores the implications of performing economy differently through reflections on an action research project undertaken in the Philippines. Here, a performative approach recreated economy as a space of decision that demands active, ethical choices (Gibson-Graham 2006) and supported relational, rather than individuated, models of economic personhood.
Anthropology
Keywords: action research; disembeddedness; economic anthropology; performative approach